2016
DOI: 10.19113/sdufbed.59206
|View full text |Cite
|
Sign up to set email alerts
|

Growth Stage and Drying Methods Affect Essential Oil Content and Composition of Pickling Herb (Echinophora tenuifolia subsp. sibthorpiana Tutin)

Abstract: The present research was conducted during 2012 in order to determine the essential oil content and composition of Echinophora tenuifolia subsp. sibthorpiana Tutin. Plants were collected during rosette, vegetative growth, full flowering and fruit-ripening stages. Oil was extracted using Clavenger hydrodistillation apparatus from either fresh, shade dried or sun dried samples. Oil composition was determined with a GC/MS. Oil content of samples showed significant variation during the vegetative stages of developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…and Echinophora tenuifolia (Guss.) Tutin revealed the influence of growth stages on the quali-quantitative composition of EOs [43,[45][46][47].…”
Section: Essential Oil Analysismentioning
confidence: 99%
“…and Echinophora tenuifolia (Guss.) Tutin revealed the influence of growth stages on the quali-quantitative composition of EOs [43,[45][46][47].…”
Section: Essential Oil Analysismentioning
confidence: 99%
“…According to these data, the greatest yield was observed at the mid‐development stage of the seeds, while the minimum yield was associated with the vegetative stages (Figure 2). Other medicinal plants such as the Apiaceae family, including Oliveria decumbens (Esmaeili et al., 2018), Trachyspermum Ammi (Soltani Howyzeh et al., 2018), and Echinophora tenuifolia (Şanli et al., 2016 ) , followed the same pattern and produced different essential oil content at various growth stages. This can be due to different physiological activities of these plants at various stages of development and its interaction with environment condition.…”
Section: Resultsmentioning
confidence: 99%
“…The final growth stage also had higher essential oil percentage, indicating the effect of different phenological stages on the essential oil percentage quality. So we can pinpoint (Kaškonienė et al, 2011;Özgüven & Tansi, 1998;Şanli et al, 2016).…”
Section: Cluster Analysis and Principal Component Analysis (Pca)mentioning
confidence: 99%
“…These plants had low essential oil content in early growth stages, while the highest essential oil content was obtained at seed setting and seed phase. Less moisture content and lower activity of some essential enzymes for biosynthesis of speci c compounds at seeding stage lead to less essential oil production at early stages of growth 28,33,34 . Furthermore, previous studies showed that essential oil content was not the same in different plant organs.…”
Section: Content Of Essential Oil and Extractsmentioning
confidence: 99%
“…The nal growth stage also had higher essential oil percentage, indicating the effect of different phenological stages on the essential oil percentage quality. So we can pinpoint the phytochemical compounds extracted from the plant strongly depend on the plant organ and phenological stage 34,47,48 . In a study to investigate the phenological effects on phytochemical compounds at different populations of the Tithonia diversifolia, the cluster and principal component analyses were used and the results showed that phytochemical compounds were differed in various phenological stages 49 .…”
Section: Chemical Compounds Of Essential Oilmentioning
confidence: 99%